Uji Kocok Cairan Lambung Untuk Diagnosis Penyakit Membran Hialin Pada Bayi Kurang Bulan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT Premature babies tend to suffer hyaline membrane disease (HMD). This condition due to insufficient surfactant production as the result of immature lung. Therefore, it is important to develop a simple method for early detection of HMD before clinical manifestation occurred. Shake test is one of the simple, easy and accurate ways to examine the maturity of lung. In order to uphold the diagnose of HMD, the result was compared with gold standard. The aim of this research was to examine the accuracy of shake test for diagnosing HMD. The design of this research was diagnostic for shake test of premature baby. The subjects of this research were 41 babies who were bom in 28-36 weeks of pregnancy from July-September 2002 in Dr. Sardjito hospital. The analysis was done by Kappa for measurement reliability with sensitivity and specificity for diagnostic test. The result of this research showed that reliability of shake test measurement with Kappa value was 0,81. Accuracy was showed with sensitivity (83,3%), specificity (88,2%), positive predictive value (90,9%) and negative predictive value (78,9%). In conclusion, shake test was quite accurate in diagnosing HMD for premature baby